2021
DOI: 10.1155/2021/6668365
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Melatonin in Female Reproduction in the Context of Oxidative Stress

Abstract: Oxidative stress has been recognized as one of the causal mediators of female infertility by affecting the oocyte quality and early embryo development. Improving oxidative stress is essential for reproductive health. Melatonin, a self-secreted antioxidant, has a wide range of effects by improving mitochondrial function and reducing the damage of reactive oxygen species (ROS). This minireview illustrates the applications of melatonin in reproduction from four aspects: physiological ovarian aging, vitrification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 98 publications
0
15
0
Order By: Relevance
“…It has been found that melatonin is present in high concentrations in human follicular fluid [ 208 ]. Melatonin has a good antioxidant effect by neutralizing free radicals and increasing the activity of antioxidant enzymes such as SOD and GSH-Px [ 209 ]. As an important endogenous antioxidant, its antioxidant properties are superior to conventional antioxidants, such as vitamin C and E [ 210 ].…”
Section: Additional Antioxidant Therapy That Can Improve Ovarian Agingmentioning
confidence: 99%
“…It has been found that melatonin is present in high concentrations in human follicular fluid [ 208 ]. Melatonin has a good antioxidant effect by neutralizing free radicals and increasing the activity of antioxidant enzymes such as SOD and GSH-Px [ 209 ]. As an important endogenous antioxidant, its antioxidant properties are superior to conventional antioxidants, such as vitamin C and E [ 210 ].…”
Section: Additional Antioxidant Therapy That Can Improve Ovarian Agingmentioning
confidence: 99%
“…Its concentration in porcine follicular fluid is approximately 10 −11 M, which is negatively correlated with follicle size, with a trend of smaller follicles and higher melatonin content ( Shi et al, 2009 ). Melatonin promotes in vitro maturation and parthenogenetic development of porcine oocytes in a dose-dependent manner, but high concentrations have negative effects ( Shi et al, 2009 ; Jin et al, 2017 ), in two ways ( Jiang et al, 2021 ). It either directly chelates oxygen and nitrogen reactive species as well as mobilizes the antioxidant enzyme in cells ( Amaral and Cipolla-Neto, 2018 ) or binds to its receptors ( Reiter et al, 2014 ) to decrease downstream molecules, such as cAMP and cGMP, as well as increase PLC ( Jockers et al, 2016 ), to mitigate oxidative stress in the female reproductive system.…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin (N‐acetyl‐5‐methoxytryptamine) is an endogenous indoleamine hormone produced mainly by the pineal gland modulating several important physiological reactions. 90 , 91 Functioning as an antioxidant, melatonin and its derivatives protects cells from oxidation, inflammation, and apoptosis. 92 …”
Section: Therapeutics Involving the Sirt Signaling Pathway To Improve...mentioning
confidence: 99%